The Impact of Job Stress on Turnover Intention with Organizational Commitment as a Mediation - Raihan Akhwan Ashshiddiqi; Jati Waskito; Muzakar Isa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of Job Stress on Turnover Intention with Affective Commitment, Continuance Commitment, and Normative Commitment as mediating variables in employees of PT. Global Foresight. This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Square (SEM-PLS) method processed through SmartPLS 3.0 software. Data were obtained from 150 respondents selected using a non-probability sampling technique with a judgment sampling type, namely, determining the sample based on certain considerations relevant to the research objectives. The results showed that Job Stress did not have a significant direct effect on Turnover Intention, but had a significant effect on the three dimensions of organizational commitment, namely Affective, Continuance, and Normative Commitment. Furthermore, Affective Commitment and Continuance Commitment were proven to have a significant effect on Turnover Intention and were able to mediate the relationship between Job Stress and Turnover Intention. Conversely, Normative Commitment did not show a significant effect on Turnover Intention and could not act as a mediator. These findings indicate that the influence of job stress on employees' desire to leave the company is more influenced by emotional attachment and considerations of job continuity than normative obligations. This research offers important implications for management in managing work stress and building employee commitment to reduce turnover rates.